Development of life skills in adolescents who practice individual sports (Research, Society and Development, 2020)
This study investigated the development of life skills of 71 adolescents who practice individual sports, with a mean age of 14.54 ± 1.27 years. The instruments used were the Life Skills Scale for Sport (P-LSSS) and a sociodemographic questionnaire. Data analysis was conducted using the Kolmogorov-Smirnov tests, independent t, MANOVA and Pearson correlation (p